TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN TAUCO DI KOTA PRABUMULIH - Rini Pradita; Yaktiworo Indriani; Achdiansyah Soelaiman (Lampung University, 2016)
The aims of this research are to analyze satisfaction level and loyalty of tauco’s customers in Prabumulih. The research was carried out in the inpres market, a traditional market in Prabumulih. The research location was chosen deliberately (purposive). The number of interviewed respondents were 60 housewives which found in the market (accidental sampling). The objective was answered by using customer satisfaction index analysis (CSI) and for customers loyalty was answered by using switcher buyer analysis, habitual buyer, satisfied buyer, liking the brand, and committed buyer. The research shows the following results, Tauco’s customers in Prabumulih are loyal customers with high satisfaction level (CSI = 71,2%) and based on Tauco’s customers loyalty pyramid, switcher buyers are only 6,7%. Key words: customers, CSI, loyality, tauco